Evaluating the Effectiveness of Virtual Reality Fire Extinguisher Training: Mixed Method Approach - Hossain, Ishtyak (My University, 2025)
Safety training is standard practice across various industries and helps reduce the number of accidents. Certain industrial tasks pose a high risk of injury, even with training, such as welding, construction, and mining. Virtual Reality (VR) can serve as an alternative solution for training scenarios in these fields since it provides a safe and engaging environment. This research conducts a mixed-method analysis to evaluate the effectiveness of VR fire extinguisher training. A hybrid experimental approach was adopted during the study, offering both practical and VR training to students. The factors considered in the effectiveness evaluation included usability, realism, engagement, knowledge acquisition, knowledge retention, and ease of navigation. Qualitative and quantitative data were analyzed jointly using Kirkpatrick’s Model and the Technology Acceptance Model. The analysis revealed that VR training successfully developed situational awareness and emergency preparedness among the trainees. The developed VR module was highly engaging and provided an interactive virtual environment. However, there were reports of navigation challenges and sensory sickness. User feedback indicated that a highly immersive VR environment with high-quality visuals and interactive components can enhance the effectiveness of VR training. The established effectiveness evaluation framework in this study can be adopted as a standard tool for evaluating further developed VR-based training modules. The findings contribute significantly to the development of VR as an alternative tool for safety training across various sectors.
Keywords: Virtual Reality, Virtual Training, Fire Safety, Mixed-Methods, Realism, Engagement, Knowledge Retention, Kirkpatrick’s Model, Technology Acceptance Model, Framework